The Effect of Information Technology, Compliance Pressure, and Auditor Experience on Audit Quality - Andi Batari Annisa Maknun; Haliah, Haliah; Nirwana, Nirwana (International Journal Of Economics Social And Technology (IJEST), 2023)
This study aims to determine the influence of information technology, compliance pressure, and auditor experience on audit quality at the Palopo City Institution. The source of the data used is primary data because it is obtained directly from the object to be studied by distributing questionnaires. Sampling using census sampling technique, because all members of the population are used as research samples, namely all auditors in the Palopo City Inspectorate. The approach used is a quantitative approach. Data analysis techniques using the help of SPSS (Statistical Package for Social Sciences) and data analysis methods using Multiple Linear Regression Analysis tests. The results of this study show that information technology and auditor experience have a positive and significant effect on audit quality, while compliance pressure has a negative insignificant effect on audit quality.